The Sense that Something has Disappeared : Nine graduates of the Department of Art. - Ayal, Avishay; Art Focus Contemporary Israeli Art, Jerusalem 1994 (Haifa : University of Haifa - Faculty of Humanities, Gallery of Art, 1994)
Raban, Tamar ; Zadok, Odelia ; Pearlman, Nina ; Azi, Asad ; Muller, Moshe ; Yasour, Penny ; Wertman, Orna ; Dubrovsky, Tamar ; Bar-Ner, Linda
The Sense that Something has Disappeared : Nine graduates of the Department of Art, University of Haifa - Faculty of Humanities, Gallery of Art, Haifa, October 11 - December 1, 1994. Art Focus Contemporary Israeli Art, Jerusalem 1994
boek